Religious Moderation from a Multiculturalism Perspective: A Systematic Literature Review - Ridwanulloh, Muhammad Syabani; Maulana, Khaidir; Adawiyah, Robiah Al; Apriyanto, Sigit (CV. Tripe Konsultan, 2025)
Religious moderation is a crucial discourse in addressing polarization and intolerance within pluralistic societies. This study systematically reviews scholarly works to examine the conceptual, practical, and policy-oriented intersections between religious moderation and multiculturalism. Employing a Systematic Literature Review (SLR) guided by PRISMA protocols, the research identified, screened, and analysed studies published from 2015 to 2025 across databases such as Scopus, Google Scholar, DOAJ, and Garuda. Inclusion criteria focused on peer-reviewed works addressing religious moderation, multicultural education, and social cohesion, while data extraction captured objectives, theoretical frameworks, methods, and findings. Thematic analysis was then applied to synthesise key patterns and gaps. The findings indicate that religious moderation, when contextualised through multicultural values, significantly enhances social integration, interfaith tolerance, and civic dialogue. Evidence suggests that its effectiveness is reinforced by educational frameworks, inclusive policy initiatives, and community-based empowerment strategies. Moreover, the analysis highlights that contextual adaptation to local culture and religious narratives is essential to ensure the acceptance and sustainability of moderation initiatives. This review concludes that embedding religious moderation within multicultural frameworks not only mitigates identity-based conflicts but also strengthens substantive democracy in diverse societies. It further underscores the necessity for policymakers, educators, and religious leaders to adopt participatory and culturally grounded strategies to promote moderation values. By mapping theoretical developments and empirical practices, this study contributes to advancing an integrative conceptual model that unites religious moderation and multiculturalism for fostering inclusive and harmonious societies.